Generation of Cisplatin-Resistant Ovarian Cancer Cell Lines: Cisplatin Resistance in Ovarian Cancer Cell Lines - Nastaran Nikounezhad,; Maryam Nakhjavani,; Farshad H. Shirazi, (Iranian Journal of Pharmaceutical Sciences, 2016)
Ovarian cancer is the most lethal gynecological cancer in which cisplatin-based treatment plays a fundamental role as the first line chemotherapy option. However, development of platinum-resistance is a critical and poorly understood problem in ovarian cancer treatment. Although in vitro generation of platinum-resistant ovarian cancer cell lines is a long established approach to uncover the molecular mechanisms underlying resistance development, the methodology of this resistance induction is poorly explained in publications. The aim of this study was to propose a method for induction of resistance in ovarian cancer cell lines. To reach this aim, A2780 human ovarian cancer cell line was continuously exposed to stepwise increasing concentrations of cisplatin (0.5–2.6μM) over a period of 6 months and three resistant sublines were collected. Cisplatin resistance was examined by clonogenic survival assay and growth curve analysis was carried out in order to evaluate the proliferation characteristics of the established sublines. The A2780 resistant sublines exhibited 5.1 to 11.7 fold resistance to cisplatin, compared to their parental cells, and although growth rate and plateau saturation density significantly decreased by cisplatin resistance enhancement, all three resistant sublines presented a typical growth curve even though they were cultured in the cisplatin containing medium. These results suggest that reliable drug resistant human ovarian cancer cell lines can be successfully established by this method.